Pengaruh Aplikasi Padlet untuk Keterampilan Menulis terhadap Berfikir Kreatif Siswa Sekolah Dasar - Shafira Fitri Azzahra; Candra Dewi; Sri Lestari (Universitas PGRI Madiun, 2022)
This study aims to determine whether the effect of padlet application on writing skills on creative thinking in fifth grade elementary school students at MIN 5 Magetan. This type of research is quantitative. Sources of data were obtained through data collected by researchers using random sampling or random sampling techniques, namely there were experimental class and control class, from this technique the sample was obtained from the number of students in class va and class vb with a total of 30 students. The data collection technique was obtained using tests and documentation. The test is in the form of questions containing statements, as well as documentation containing the syllabus, lesson plans, and so on. The results of this study indicate the acquisition of data and the discussion that has been explained that there is an effect of using the padlet application for writing skills on the creative thinking of fifth grade elementary school students with data evidence of hypothesis testing results, namely the results of significant 0.001 < 0.05 then H0 is rejected and Ha is accepted. So, it can be concluded that there is a significant effect on the padlet application for writing skills on the creative thinking of fifth grade elementary school students at MIN 5 Magetan. The findings in the results of this research are that students say that the padlet application is easy to use because it is available for free on online and playstore platforms and is also easy to use. In addition, it trains students to think creatively in writing a descriptive essay.